The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1063/1.1141037
|View full text |Cite
|
Sign up to set email alerts
|

Delay-time modulation spectroscopy using a cw mode-locked Nd:YAG laser synchronized with the synchrotron radiation pulses (invited)

Abstract: Picosecond light pulses synchronized with successive pulses of synchrotron radiation have been generated using a cw mode-locked Nd:Y AG laser. By improvement of the time characteristics of the synchronized pulses, transient absorption measurements have been made in a short time domain of 0.05-11 ns using a delay-time modulation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The standard synchrotron storage ring generates tens of megahertz optical pulse trains with each pulse having the pulse duration of tens to hundreds of picoseconds. One of the authors reported 22 an electronic synchronization for the pump-probe measurement between the SR and picosecond laser pulses with a time resolution of 500 ps ͑limited by the SR pulse duration͒. Recent commercial femtosecond lasers with an electronic synchronization system can restrict the timing jitter to an external signal within several picoseconds.…”
Section: A Possible Extention To a Combination Of The Synchrotron mentioning
confidence: 99%
“…The standard synchrotron storage ring generates tens of megahertz optical pulse trains with each pulse having the pulse duration of tens to hundreds of picoseconds. One of the authors reported 22 an electronic synchronization for the pump-probe measurement between the SR and picosecond laser pulses with a time resolution of 500 ps ͑limited by the SR pulse duration͒. Recent commercial femtosecond lasers with an electronic synchronization system can restrict the timing jitter to an external signal within several picoseconds.…”
Section: A Possible Extention To a Combination Of The Synchrotron mentioning
confidence: 99%
“…The development of versatile methodology for highly time-resolved measurements is therefore a subject of practical interest. The primary requirement for realizing well controlled timing between two photon sources is to synchronize them, and indeed much effort has been made since the early days of the development of synchrotron storage rings (Meyer et al, 1987;Mitani et al, 1989;Lacoursiere et al, 1994;Gatzke et al, 1995Gatzke et al, , 1998Winter et al, 1998;Tanaka et al, 2000). For construction of rigid electronic synchronization, the laser should be kept in a very stable mode-locked operation, including fine and fast mechanical control of cavity length to compensate for the fluctuation in pulse frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Already done in the solid-state [7] and liquid phase [8] but never yet in the gas phase where the target density is very low, a time-resolved laser+synchrotron experiment is presented here on a simple test system : helium. The experimental set-up is described in detail elsewhere [9].…”
Section: The Experimentsmentioning
confidence: 99%